Amoris Laetitia Develops the Subjective Conscience from Veritatis Splendor - Matthew P. Schneider (Journal of Moral Theology)
The subjective and objective aspects of conscience often exist in tension in Catholic theology: there is a need to affirm that an objective law exists by which proper conscience formation is judged, while acknowledging a subjective aspect in each person, obliged to follow her, even erroneous, conscience. Although not the focus of either _Veritatis Splendor_ or _Amoris Laetitia_, these two papal documents demonstrate these dual aspects of conscience well and allow a better understanding of conscience together than they could apart. Reading each in light of the other provides a fuller view and illuminates the tension between the two aspects of conscience. _Veritatis Splendor_ provides a clear explanation of the objective aspect of conscience while briefly mentioning the subjective. _Amoris Laetitia_ briefly reaffirms the objectivity of conscience and then dramatically expands on its subjectivity, spending significant time on mitigating factors and the formation of conscience as both a starting point and an end goal. This paper analyzes these documents in dialogue with Charles Curran as contrary view to the two popes.